Shiga Toxin-Producing Escherichia coli Infection in Jönköping County, Sweden: Occurrence and Molecular Characteristics in Correlation With Clinical Symptoms and Duration of stx Shedding - Bai, Xiangning; Mernelius, Sara; Jernberg, Cecilia; Einemo, Ing-Marie; Monecke, Stefan; Ehricht, Ralf; Löfgren, Sture; Matussek, Andreas (Frontiers in Cellular and Infection Microbiology, 2018)
Shiga toxin–producing Escherichia coli (STEC) cause bloody diarrhea (BD), hemorrhagic colitis (HC), and even hemolytic uremic syndrome (HUS). In Nordic countries, STEC are widely spread and usually associated with gastrointestinal symptoms and HUS. The objective of this study was to investigate the occurrence of STEC in Swedish patients over 10 years of age from 2003 through 2015, and to analyze the correlation of critical STEC virulence factors with clinical symptoms and duration of stx shedding. Diarrheal stool samples were screened for presence of stx by real-time PCR. All STEC isolates were characterized by DNA microarray assay and PCR to determine serogenotypes, stx subtypes, and presence of intimin gene eae and enterohaemolysin gene ehxA. Multilocus sequencing typing (MLST) was used to assess phylogenetic relationships. Clinical features were collected and analyzed using data from the routine infection control measures in the county. A total of 14,550 samples were enrolled in this 12-years period study, and 175 (1.2%) stools were stx positive by real-time PCR. The overall incidence of STEC infection was 4.9 cases per 100,000 person-years during the project period. Seventy-five isolates, with one isolate per sample were recovered, among which 43 were from non-bloody stools, 32 from BD, and 3 out of the 75 STEC positive patients developed HUS. The presence of stx2 in both stools and isolates were associated with BD (p = 0.008, p = 0.05), and the presence of eae in isolates was related to BD (p = 0.008). The predominant serogenotypes associated with BD were O157:H7, O26:H11, O121:H19, and O103:H2. Isolates from HUS were O104:H4 and O98: H21 serotypes. Phylogenetic analysis revealed our strains were highly diverse, and showed close relatedness to HUS-associated STEC collection strains. In conclusion, the presence of stx2 in stool was related to BD already at the initial diagnostic procedure, thus could be used as risk predictor at an early stage. STEC isolates with stx2 and eae were significantly associated with BD. The predominant serotypes associated with BD were O157:H7, O26:H11, O121:H19, and O103:H2. Nevertheless, the pathogenic potential of other serotypes and genotypes should not be neglected.